A Classification of Deafness Based on the Effect of Deafness on Efficiency in Life - Love, J. Kerr (1929)
The deaf classified from the point of view of incapacity as a result of deafness: (a) The true deaf-mute; developmental.—(b) The muted or semi-muted, totally deaf because of disease occurring shortly after birth.—(c) The speaking deaf, totally deaf from disease occurring after two years of age.—(d) Partially deaf, hard of hearing. Hearing tests useless except in (d).—Treatment useless except in (d). Syphilis: its association with congenital deafness; percentage due to this cause, in children. Incapacity due to deafness.—Aids to hearing.—Prevention of deafness.